Mucocele of the lower lip in a 70 y.o. patient with poorly fitted denture – a case report - Osica, Piotr; Osica, Karolina; Janas-Naze, Anna (Journal of Education, Health and Sport, 2018)
The article presents a case of 70-year-old patient with mucocele of lower lip caused by poorly fitted denture.